Associations of plasma carnitine, lysine, trimethyllysine and glycine with incident ischemic stroke: Findings from a nested case-control study. Issue 9 (September 2022) - Liu, Dong; Wang, Jingyuan; Xiao, Liju; Gu, Siyu; Ma, Ze; Zhou, Zhengyuan; Gu, Shujun; Zuo, Hui
Summary: Background & aims: Carnitine biosynthesis has been related to fatty acid oxidation, a process probably exerting neuroprotective effects. However, the role of carnitine biosynthesis in the development of ischemic stroke (IS) remains unclear. We aimed to examine the associations between plasma markers of carnitine biosynthesis and the IS risk. Methods: We performed a case-control study nested in a community-based cohort (2013–2018, n = 16457). The study included 321 incident cases of IS and 321 controls matched by age and gender. Carnitine, lysine, trimethyllysine (TML), glycine, and their ratios were measured/calculated in the baseline plasma samples using ultra-high performance liquid chromatography–tandem mass-spectrometry (UHPLC–MS/MS). Conditional logistic regression analyses were used to calculate odds ratios (ORs) and their 95% confidence intervals (CIs). Results: Plasma carnitine, lysine, TML, and glycine were not significantly associated with the IS risk, although a gradually reduced risk was observed across the increasing tertiles of glycine. Notably, the ratios of glycine/carnitine, glycine/lysine, and glycine/TML were all inversely associated with the IS risk. Compared to the lowest tertiles, the corresponding odds ratios for the highest tertiles were 0.60 (95% CI: 0.40–0.91), 0.63 (95% CI: 0.42–0.94), and 0.63 (95% CI: 0.42–0.95), respectively, after adjustment for body mass index, smoking, hypertension, family history of stroke, estimated glomerular filtration rate and total cholesterol. Repeating the analyses by excluding the first two years of follow-up did not materially alter the risk associations for the ratios of glycine/lysine and glycine/carnitine. Conclusions: Increased ratios of plasma glycine to carnitine, lysine, and TML were associated with a lower risk of incident IS. Our observational findings suggest that the homeostasis of circulating carnitine, lysine, TML, and glycine may involve in the pathogenesis of IS.